Jakarta Eastplora: Website for Exploring Destinations in East Jakarta - Sahara, Siti; Ninvika, Dhiwa Humaira; Junitasari, Yolanda (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Jakarta Eastplora is a digital platform developed to provide detailed information about tourist destinations in East Jakarta. This study adopts a Research and Development (R&D) approach using the ADDIE model, which consists of five key stages: Analysis, Design, Development, Implementation, and Evaluation. The primary objective of developing Jakarta Eastplora is to offer users easy and comprehensive access to destination information in East Jakarta, focusing on enhancing user experience through interactive features and intuitive design. The platform is also designed to be an effective promotional tool in supporting local tourism and economic growth. During the development process, user needs were analyzed to determine relevant features, while the evaluation stage was used to identify areas for improvement and ensure the platform's quality. The results of this study indicate that Jakarta Eastplora successfully meets users' informational needs and has significant potential in supporting destination exploration and economic development in East Jakarta. The platform can also be regularly updated to maintain its relevance and effectiveness over the long term.